Association of Awake Bruxism with Khat, Coffee, Tobacco, and Stress among Jazan University Students - Mir Faeq Ali Quadri; Ali Mahnashi; Ayman Al Almutahhir; Hamzah Tubayqi; Abdullah Hakami; Mohamed Arishi; Abdulwahab Alamir (Hindawi Limited, 2015)
Objective. The objective is to assess the prevalence of bruxism among the university students and to check its association with their khat chewing habit. Materials and Methods. A cross-sectional descriptive study is designed using cluster random sampling. Pretested questionnaire was administered by a trained interviewer to assess awake bruxism and the use of variables like khat, coffee, tobacco, and stress. Chi-square test at 5% significance was used for assessing the association. Logistic regression was also performed after adjusting for covariates. Results. A high response rate (95%) was obtained as the distribution and collection of questionnaire was within an hour interval. 85% (63%, males; 22%, females) experienced an episode of bruxism at least one time in the past six months. Regression analysis revealed an association of stress (P=0.00; OR = 5.902, 95% CI 2.614-13.325) and khat use (P=0.05; OR = 1.629, 95% CI 0.360-7.368) with bruxism. Interestingly, it is observed that the one who chew khat experienced 3.56 times (95% CI; 2.62-11.22) less pain when compared to the nonusers. Conclusion. This study is the first of its kind to assess the association of bruxism with khat chewing. High amount of stress and khat use can be considered as important risk indicators for awake bruxism.